A Need Analysis MOOC for Based Instructional Material in Flipped English Speaking Class at Indonesian Higher Education - Andi Agusniati; Areski Wahid; Rafi'ah Nur; Asdar Asdar (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This research aims to find out the characteristics of MOOC-based instructional material for the flipped English speaking class and the model of MOOC-based instructional materials for flipped English speaking class The researchers implemented the initial phase of qualitative research to achieve their objectives. The study focused on students in the English Language Education (ELE) Department at Indonesian Higher Education, as well as the ELE program's lecturers. The findings revealed that the MOOC-based materials for the flipped-English speaking class were a need analysis to be supportive, accommodating, goal-oriented, and focused on both fluency and accuracy. These materials were diverse, up-to-date, engaging, and motivating. They included both monologues and dialogues suitable for formal and informal contexts, and also incorporated tools relevant to the Fourth Industrial Revolution, such as WhatsApp and Edmodo. The proposed model for MOOC-based materials in the flipped-English speaking class emphasized the integration of key elements: goals, content, activities, venue, and media. The goal was to help learners become proficient in speaking by mastering content that included various topics, language uses, and genres. The model engaged students in nine activities: guessing I, identifying, searching, finding, guessing II, clarifying, evaluating, reflecting, and projecting. The recommended learning venues were both online (using platforms like WhatsApp and Edmodo) and offline (such as classrooms, language labs, and outdoor settings). For media, the model suggested using laptops, LCD projectors, and leaflets during the learning sessions.